Agro-Morphological Diversity of White Roselle (Hibiscus sabdariffa var. altissima) for Climate Change Adaptation in Burkina Faso - Dramane Kabore; Adama Rama (AgroEnvironmental Sustainability)
Climate change intensifies the variability of agroclimatic conditions in sub-Saharan Africa, threatening food security through increased droughts, rainfall gaps, and soil degradation. In this context, endogenous adaptation approaches based on local resources, such as White Roselle (Hibiscus sabdariffa var. altissima), are strategic due to their hardiness and dual food and textile uses. This study aims to characterize the agro-morphological diversity and performance stability of ten local white roselle cultivars from Burkina Faso to identify genotypes best adapted to contrasting climatic environments. The experiment was conducted over two agricultural seasons, dry and wet, in three locations with distinct ecological conditions. A randomized complete block design with three replications was implemented. Thirteen agro-morphological traits were measured. Data were analyzed using multifactor ANOVA, Tukey's HSD test for pairwise comparisons, calculation of the amir index, and stability analyses based on Finlay-Wilkinson and Ammi methods. Results showed a significant influence of cultivar and site factors. Kongkrou, Nikiema, and Konde exhibited good performance and high stability. Bakaridjan and Bala were more sensitive to environmental variations. These findings highlight the importance of valorising local cultivars in breeding strategies for resilient agriculture in West Africa.